Project led education in engineering courses : competencies to include - Hattum-Janssen, Natascha van (2007)
As a result of the implementation of the Bologna Declaration and the growing emphasis on lifelong learning in a knowledge society, project education has been implemented in a number of engineering courses at the University of Minho. The degree to which the project is influencing the curriculum varies from course to course. In some course, the project is a project exercise in which already acquired knowledge is applied, in others, the project is the leading element of the semester and other subjects depend entirely on the project. In each case, the project has to be designed in such a way that all or most subjects of the semester are to some extent represented in the project. The competencies as developed for the project have to meet several requirements. In the first place, they have to be based in the subjects or content areas that form the project. They also have to fit within the general framework of the course and general project specifications of a particular semester. Apart from these demands, each project has to meet a number of specific requirements, related to the problem to be solved during the project: the solution needs to “work”. Finally, the competencies defined in project education need to represent a number of soft skills. The article explores three student guides and the kind of competencies involved in three different project learning experiences.